The Influence of Target Games Training and Target Service Training of The Wall With Targets on Ability The Service Accuracy - Didik Purwanto; Ardiansyah D. Kandupi; Nyoman Sukrawan (UNIVERSITAS NEGERI MAKASSAR, 2023)
The main objective of this research is to analyze the effect of target game practice and over-the-wall practice to increase the accuracy of the top serve. This research was conducted on 30 students participating in volleyball extracurricular activities at SMAN 1 Balinggi. There were three groups, each group numbering 10 people, namely group 1 was given target game practice, group 2 was given training on serving against the wall with a target and the control group. Data retrieval is done by testing the service accuracy using the service accuracy test. Data analysis used paired t-test and Way ANOVA with = 0.05. Results: there is a significant effect of target game practice on the accuracy of the upper serve with a sig value of 0.000 <0.05. There is a significant effect of top-serve training with a target on the accuracy of the top service with a sig value of 0.000 <0.05. There was a significant difference between the three groups in the accuracy of serving over 18.894>t3.39. Group 1 was better than Group 2 and Group 3 in improving their top serve accuracy. Conclusion: There is a significant effect of target game practice and over-the-wall practice with targets in improving the accuracy of the top serve.